2013
DOI: 10.1016/j.bpj.2012.11.3817
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Radiation Damage Limit with Cryo-SAXS

Abstract: Small angle x-ray scattering (SAXS) is a versatile and widely used technique for obtaining low-resolution structures of macromolecules and complexes. SAXS experiments measure molecules in solution, without the need for labeling or crystallization. However, radiation damage currently limits the application of SAXS to molecules that can be produced in microgram quantities; for typical proteins, 10-20 μL of solution at 1 mg/mL is required to accumulate adequate signal before irreversible x-ray damage is observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 59 publications
5
78
0
Order By: Relevance
“…A typical x-ray dose soft matter samples might withstand is on the order of 400 Gy (lysozyme in aqueous solution) to 500 kGy (lysozyme crystal). 31 Therefore, we conclude that the stability of our IL sample with respect to x-ray radiation damage lies in the typical range for a soft matter system.…”
Section: Radiation Damagementioning
confidence: 65%
“…A typical x-ray dose soft matter samples might withstand is on the order of 400 Gy (lysozyme in aqueous solution) to 500 kGy (lysozyme crystal). 31 Therefore, we conclude that the stability of our IL sample with respect to x-ray radiation damage lies in the typical range for a soft matter system.…”
Section: Radiation Damagementioning
confidence: 65%
“…However, it was also found that early effect of radiation damage was an increase of molecular size without any significant unfolding suggesting that radiation damage observed on BSA was compatible with the presence of radical activities [61]. Reduction in radiation damage has been obtained using Cryo-SAXS [12] or using time-resolved SAXS [62]. Besides, fast detection readout allows collection of SAXS before radiation damage occur [60].…”
Section: Discussionmentioning
confidence: 99%
“…When planning combined experiments, it is important to consider the effects of X-ray exposure, both short and long term, related to the bioSAXS experiment [11, 12]. BioSAXS data is routinely checked for short term variations during exposure and shows there is no variation on the length scales (low resolution size and shape) and time scales (1–10 s at dedicated facilities).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SAS is essentially a low‐information technique, combining SAS with complementary techniques can circumvent this limitation in many cases . However, much work remains in method developments for data acquisition, analysis and model validation . In the coming years, modern X‐ray sources and methodological advances will probably open up unprecedented ways to reconstruct solution structures of biomacromolecules, and will conceivably reveal unforeseen wealth of information on protein motion, which will be a giant step forward …”
Section: Discussionmentioning
confidence: 99%